Black internationalist feminism : women writers of the Black left, 1945-1995 - Higashida, Cheryl (University of Illinois Press, 2011)
'Black Internationalist Feminism' examines how African American women writers affiliated themselves with the post-World War II Black Communist Left and developed a distinct strand of feminism.